Wpisani w krajobraz naukowy - "Zielonogórskie Studia Bibliotekoznawcze" = Inscribed in the scientific landscape - "Zielona Góra Library Science Studies" - Jamrozik, Katarzyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
"Zielona Góra Library Science Studies" has been published since 2002 by Regional and Municipal Cyprian Norwid`s Public Library in Zielona Gora. The first four notebooks of this scientific periodical were historico-bibliographical monographies, tightly connected with the regional problematics. In the first volume Grzegorz Chmielewski presented the history of Polish folk libraries on the West border, in the second one - Janusz Rećko prepared the detailed description of Włodzimierz Korsak`s archives, in the third one - Dawid Kotlarek juxtaposed the bibliography of Zielona Gora in the German writings until 1945, in the next volume Jarosław Kuczer worked out the collection of correspondence by Hermina von Reuss.`
Keywords: "Zielonogórskie Studia Bibliotekoznawcze"; czasopisma naukowe; czasopisma bibliotekoznawcze; "Zielona Góra Library Science Studies"; scientific magazines; library; science magazines